Demands for Media Democratisation and the Latin American 'New Left': Government Strategies in Argentina and Brazil in Comparative Perspective - Philip Kitzberger (German Institute of Global and Area Studies (GIGA), 2014)
This paper examines the determinants of government strategies vis-à-vis dominant media actors in the Latin American context, where the media's role in democratic politics is increasingly being questioned. It compares the first two Kirchnerist presidencies in Argentina with the first two Workers' Party-led governments in Brazil. While these governments initially adopted accommodation strategies towards media organisations, political crises subsequently disturbed the fragile coexistence of media and government, triggering divergent strategic responses that require explanation. Using accounts relying on ideological preferences, the study establishes the importance of environmental factors and critical junctures as determinants of governments' strategic options. Significant differences in the institutional configurations and articulations of media interests in the two countries are found to be relevant. However, the study shows that such constraints do not tell the whole story. Consequently, the analysis also focuses on how certain junctures affect government perceptions of media power and, in turn, inform governments' strategic stances.
Keywords: 300; Argentina; Brazil; media politics; government strategy; democratisation